2009
DOI: 10.1097/hjh.0b013e3283310f92
|View full text |Cite
|
Sign up to set email alerts
|

Renal and cardio-protective effects of direct renin inhibition: a systematic literature review

Abstract: Evidence from preclinical and clinical studies suggests that DRIs may have renal and cardiovascular effects beyond their ability to lower blood pressure. Results of ongoing hard outcome trials are awaited to definitively assess the renal and cardio-protective effects of these agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 97 publications
(188 reference statements)
0
5
0
1
Order By: Relevance
“…NT-proBNP, BNP, PRA, PRC, aldosterone are all biological markers connected tightly with heart failure. Of them, NT-pro BNP and BNP levels are particularly important, and can be used to evaluate the severity of disease [27]. However, when evaluating cardiovascular outcomes in HF patients, our results showed that compared with placebo, aliskiren showed no obvious effects on death rate, the incidence of myocardial infarction and stroke.…”
Section: Main Findings and Possible Explanationsmentioning
confidence: 67%
“…NT-proBNP, BNP, PRA, PRC, aldosterone are all biological markers connected tightly with heart failure. Of them, NT-pro BNP and BNP levels are particularly important, and can be used to evaluate the severity of disease [27]. However, when evaluating cardiovascular outcomes in HF patients, our results showed that compared with placebo, aliskiren showed no obvious effects on death rate, the incidence of myocardial infarction and stroke.…”
Section: Main Findings and Possible Explanationsmentioning
confidence: 67%
“…Alterations in renin activity have been associated with hypertension, salt-sensitivity of blood pressure and responsiveness to anti-hypertensive treatments 13 . Therefore, the renin gene (REN) is a rational candidate for unraveling the genetic basis of essential hypertension (EH).…”
Section: Introductionmentioning
confidence: 99%
“…However, renin inhibitors do regulate renal perfusion. When used either alone or in combination with other RAS inhibitors, direct renin inhibition clearly increases renal plasma flow, reduces albuminuria, and improves cardiovascular parameters such as total peripheral resistance, arterial pressure, and left ventricular mass index [48]. In healthy volunteers, renin inhibitors increase renal blood flow by nearly 70% more than ACE inhibitors [49].…”
Section: Management Of Hypertension In Diabetes: a Microcirculation Amentioning
confidence: 99%